2015
DOI: 10.2139/ssrn.2665830
|View full text |Cite
|
Sign up to set email alerts
|

Does Age-Related Decline in Ability Correspond with Retirement Age?

Abstract: is to produce first-class research and forge a strong link between the academic community and decision-makers in the public and private sectors around an issue of critical importance to the nation's future. To achieve this mission, the Center sponsors a wide variety of research projects, transmits new findings to a broad audience, trains new scholars, and broadens access to valuable data sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…This finding is very consistent with research showing a strong impact on retirement of physically demanding work (Modrek, & Cullen, 2012) and physical limitations (Belbase et al, 2015), but is one of the first studies to specifically examine the interaction effect.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This finding is very consistent with research showing a strong impact on retirement of physically demanding work (Modrek, & Cullen, 2012) and physical limitations (Belbase et al, 2015), but is one of the first studies to specifically examine the interaction effect.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, jobs that have more cognitive demands tend to be associated with white-collar work and could therefore be associated with much later retirement if demands do not exceed resources (Fisher et al, 2014). Although workers’ personal resources can certainly be more broadly construed (Hobfoll, 2002), physical, emotional, and cognitive functioning are all important resources that may help workers with meeting their job demands and, in turn, their ability to stay on the job to older ages (Belbase, Sazenbacher, & Gillis, 2015; Jex, Wang, & Zarubin, 2007). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, construction workers in a number of countries have been found to stop working at an earlier age than other workers [Brenner and Ahern, ; Liira et al, ; Capanni et al, ; Welch, ; Järvholm et al, ]. In a recent study, Belbase et al [] demonstrated that blue‐collar workers were especially susceptible to early declines in ability that inhibit their ability to work to the full retirement age under the current Social Security policy.…”
Section: Introductionmentioning
confidence: 99%
“…(2017) study the effect of mismatches between actual abilities and job demands on retirement expectations focusing, by necessity, on a limited number of dimensions, rather than a comprehensive assessment of mismatches between multiple job demands and actual level of abilities. Using the same data sources, Belbase et al (2015) construct a susceptibility index, which captures how likely the abilities required for an occupation are to decline with age for all occupations in the economy. By relating the index to retirement behaviors, they find that workers in occupations that rely more on abilities with faster age-decline tend to retire earlier.…”
Section: Introductionmentioning
confidence: 99%